Endoscopic gastrostomy: critical analysis in a regional referral hospital - Marques Fávaro, Gabriel (2017)
Introduction: Percutaneous endoscopic gastrostomy (PEG) is a safe and effective endoscopic surgical procedure for enteral access and gastrointestinal decompression, and it is an excellent alternative to surgical gastrostomy. There are various clinical indications and these mainly include the need for prolonged enteral nutritional support due to complications from neurological, geriatric and oncological diseases and decompression of the gastrointestinal tract. Although safe and effective, a number of possible complications relating to the time (early or late complications) and severity (minor or major complications) may occur. Objective: To evaluate the indications and complications relating to PEG among selected patients at the digestive endoscopy service of a regional referral hospital. Materials and methods: A retrospective study on patients who underwent PEG between May 2013 and April 2015 was conducted. The patients were identified through searching the medical records and using a standardized data form. Results: 53 cases were analyzed. The average age was 70.47 years and 60.37% of the patients were women. The main indication identified was the need for enteral nutritional support, and 73.58% of these indications were derived from neurological complications, 15.09% from geriatric complications and 9.43% from oncological complications and 1.88% were due to gastrointestinal decompression. Complications occurred in 24.52% of the cases: 23.07% were major and 76.93% were minor. Regarding the time, there were eight cases of late complications and five of early complications. Conclusion: PEG was shown to be an effective and safe method for enteral access. The indication and complication rates were similar to those reported in the literature.